2019
DOI: 10.3390/su11246895
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Teacup Shape on the Cognitive Perception of Tea, and the Sustainability Value of the Aesthetic and Practical Design of a Teacup

Abstract: The ceramic industry is among the most profitable industries in the world, but, because of the use of nonrenewable materials and high fuel consumption, it also has a carbon footprint. Ceramic materials account for the majority of drinking vessels. Several scholars found that consumers’ awareness of drinks and purchasing desires are highly correlated with a vessel’s shape and color—in other words, the visual stimulation. However, since prior studies have focused on alcohol, bubble drinks, juice, coffee, cocoa, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 60 publications
0
5
1
Order By: Relevance
“…In contrast to Van Doorn et al's work, the thickness of the teacup did have effect on the tea taste and fragrance in this present study. Despite some literature [52,55,56] suggesting that the flavor of coffee, beverage and tea is associated with the height of vessels, the present study found the height of teacup had no impact on tea taste and fragrance in both groups. Chinese tea is always hot, so the standard steps of drinking Chinese tea is to observe the tea color, smell it, and then taste it.…”
Section: Hypothesis Resultscontrasting
confidence: 99%
“…In contrast to Van Doorn et al's work, the thickness of the teacup did have effect on the tea taste and fragrance in this present study. Despite some literature [52,55,56] suggesting that the flavor of coffee, beverage and tea is associated with the height of vessels, the present study found the height of teacup had no impact on tea taste and fragrance in both groups. Chinese tea is always hot, so the standard steps of drinking Chinese tea is to observe the tea color, smell it, and then taste it.…”
Section: Hypothesis Resultscontrasting
confidence: 99%
“…The methods for brewing tea from different types of tea leaves differ slightly. In a study [20], the tea-brewing method recommended by the Tea Research and Extension Office of Agriculture and Food Agency of the Executive Yuan was adopted for an experiment. The method involves adding 3 g of tea leaves into a white porcelain cup, adding 150 mL of boiling water at 100 • C, and then steeping the leaves for 5 min.…”
Section: The Methods For Brewing Oolong Tea In Taiwanmentioning
confidence: 99%
“…Teacups and teapots are the essential tea utensils used for tea brewing. Teacups possess aesthetic and artistic value, and the cup shape affects the mouthfeel while drinking tea [20]. Modern teacups have diverse shapes and styles, and people may use ornamental or functional tea utensils while brewing tea; such utensils include serving pitchers, tea chopsticks, tea scoops, and tea sticks [17].…”
Section: Features Of Taiwanese Tea Utensils Setmentioning
confidence: 99%
“…The tea culture is an exceptional traditional Chinese culture, which involves the production and consumption of tea in China. Literature [10] integrates the thinking and methods of expert users and designers into the design of tea utensils, and combines the fuzzy set qualitative comparative analysis method to study the influence of the visual design of Chinese tea containers on the taste of beverages, which is conducive to the promotion of the development of the Chinese tea culture while mapping out the concept of "practical beauty". In addition, tea culture helps to cultivate sentiment, literature In addition, aesthetic education is the combination of aesthetic teaching and beauty teaching, which enhances people's ability to recognize, understand, appreciate, and create beauty through education, and is the embodiment of cultivating morality, intelligence, physical fitness, and aesthetics in the new era.…”
Section: Review Of Relevant Studiesmentioning
confidence: 99%